Oral History Program Interview: Loye Lucille Martin Holmes - Holmes, Loye Lucille Martin
Holmes was born in Wayside, Oklahoma in 1917. After sterilizing any items containing cotton, she and her family passed the border check-points without harassment and settled in Arvin, California in 1936. Her interview includes descriptions of grass housing, ditch camps, and government camps; her thoughts on welfare during the Great Depression; how the WPA helped her family; home remedies; a woman's perspective in an abusive relationship; organizing and striking in the fields; discrimination as an "Okie;" and what made The Grapes of Wrath mostly true.